2017
DOI: 10.1002/anie.201710899
|View full text |Cite
|
Sign up to set email alerts
|

In‐Situ Microfluidic Study of Biphasic Nanocrystal Ligand‐Exchange Reactions Using an Oscillatory Flow Reactor

Abstract: Oscillatory flow reactors provide a surface energy-driven approach for automatically screening reaction conditions and studying reaction mechanisms of biphasic nanocrystal ligand-exchange reactions. Sulfide and cysteine ligand-exchange reactions with as-synthesized CdSe quantum dots (QDs) are chosen as two model reactions. Different reaction variables including the new-ligand-to-QD ratio, the size of the particles, and the original ligand type are examined systematically. Based on the in situ-obtained UV/Vis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Microfluidic reactors allow for the addition of multiple reagents in a user-defined manner, rapid thermal and mass transfer, and quantitative kinetic investigation of reactions, thus defining an ideal medium for preparing semiconductor NCs with well-defined morphologies and physicochemical properties. 100 103 In addition, the advances in robust microfluidic configurations, 100 , 103 real-time detection methods, 104 111 continuous purification 112 , 113 and ligand-exchange 114 systems, and optimization algorithms 115 117 make microfluidic reactors ideal for the detailed investigation of rapid and complex reaction kinetics 77 , 78 , 106 , 118 and for the discovery of multicomponent semiconductor NCs. 77 , 78 , 119 …”
Section: Resultsmentioning
confidence: 99%
“…Microfluidic reactors allow for the addition of multiple reagents in a user-defined manner, rapid thermal and mass transfer, and quantitative kinetic investigation of reactions, thus defining an ideal medium for preparing semiconductor NCs with well-defined morphologies and physicochemical properties. 100 103 In addition, the advances in robust microfluidic configurations, 100 , 103 real-time detection methods, 104 111 continuous purification 112 , 113 and ligand-exchange 114 systems, and optimization algorithms 115 117 make microfluidic reactors ideal for the detailed investigation of rapid and complex reaction kinetics 77 , 78 , 106 , 118 and for the discovery of multicomponent semiconductor NCs. 77 , 78 , 119 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Hersam et al. demonstrated that the same approach could be expanded to exfoliate bulk BP, another class of layered 2D semiconductors . BP shows a high charge‐carrier mobility but is readily oxidized under ambient conditions, which hinders its practical use.…”
Section: Exfoliation Approachesmentioning
confidence: 99%
“…Until recently, a detailed kinetic understanding of heterogeneous ligand exchange reactions was limited by the labor-intensive phase separation and purification required for offline spectroscopic measurements. Using a single-droplet oscillatory microfluidic reactor with online absorption spectroscopy, Shen and Abolhasani et al [122] studied the biphasic ligand exchange kinetics of oleate (OA)-and octadecylphosphonic acid (ODPA)-capped CdSe QDs (in toluene) with sulfide anions (in formamide), shown in Figure 7C panel I. Because of a difference in the relative velocity of the engulfed polar phase (formamide) and the wetting phase (toluene), the polar phase displaced to the front of the biphasic droplet at the ends of the horseshoe-shaped microfluidic reactor, allowing for straightforward delineation of each phase for online UV-vis absorption analysis.…”
Section: Surface Functionalizationmentioning
confidence: 99%